Caracterização de aerossóis no Pantanal Mato-Grossense - Santos, Anna Carolinna Albino (2014)
The Pantanal is a region of enormous ecological and socioeconomic importance. The Pantanal is the largest wetland existing continuous and has been showing interest in climate-related studies to understand the anthropogenic and natural mechanisms that are able to regulate the composition of the atmosphere. Can assess the impact of fires and especially to determine the seasonal variability of aerosol concentration in this region. The purpose of this study was to characterize the aerosol elemental composition, the seasonal variability of concentrations, and to evaluate the sources of particulate matter in the Pantanal Mato Grossense. Atmospheric aerosol samples were collected from April 2012 to August 2013 at Baía das Pedras, located in Pantanal, Brazil. The sampling device consisted of particulate samplers (SFU – stacked filter units), which separates the fine fraction ( dp ˂ 2.5 μm ) and the coarse fraction ( 2,5 - 10 μm ) of the aerosols. The elemental analysis was done using X- ray fluorescence by dispersive energy. Three types of aerosol sources were determined for both seasons by PMF (Positive Matrix Factorization) analysis: natural biogenic emissions, resuspension of soil dust, and biomass burning, being sources of fine and coarse particles. In the dry season there was an average of 0.00866 μg/m3 for fine particulate matter and 0.00721 μg/m3 for coarse particulate matter. A known fraction of MPF represented 20.8 % of its mass in the dry season, with an MPG represented 20.1 %. In the rainy season there was an average of 0.00424 μg/m3 for MPF and 0.00544 μg/m3 for MPG. A known fraction of MPF represented 24.5% and MPG, 23.8%.